Chinese Younger Parents' Quality of Life During the COVID-19 Pandemic: Do Job Changes and Family Conflicts Matter? - Liu, Xiaohan; Bai, Yashuang; Huang, Ning; Ahmed, Farooq; Shahid, Muhammad; Guo, Jing (Frontiers in Public Health, 2022)
The quality of life might have been decreased owing to the social disruptions in daily life and basic functioning after Coronavirus Disease (COVID-19) pandemic. This study aims to examine the relationship between job changes, family conflicts, and quality of life among parents during COVID-19 in China. We recruited 1209 adults through an online cross-sectional survey in China during the COVID-19 lockdown from April 21st to April 28th, 2020. Convenient and cluster sampling methods were used to recruit parents. The global health items in the Patient-Reported Outcomes Measurement Information System (PROMIS) were used as a measurement for quality of life. Data were mainly analyzed by multiple linear regression with SPSS. Both marital conflict (β=-0.243, P<.001) and parent-child conflict (β=-0.119, P=.001) were negatively associated with the quality of life among parents during the lockdown. While job changes moderated the relationship of marital conflict and quality of life (β=-0.256, P=.022). Besides, the interaction effects of job changes and family conflict on quality of life only significantly among fathers and one child families. This study indicated the family conflict was a crucial factor correlated with quality of life among young parents in the backdrop of COVID-19 lockdown. Job changes could interact with marital conflict and parent-child conflict on quality of life.